2016
DOI: 10.18632/oncotarget.9814
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of glycolysis and oxidative phosphorylation in benzo[β]pyrene and arsenic-induced rat lung epithelial transformed cells

Abstract: Arsenic and benzo[β]pyrene (B[a]P) are common contaminants in developing countries. Many studies have investigated the consequences of arsenic and/or B[a]P-induced cellular transformation, including altered metabolism. In the present study, we show that, in addition to elevated glycolysis, B[a]P/arsenic-induced transformation also stimulates oxidative phosphorylation (OXPHOS). Proteomic data and immunoblot studies demonstrated that enzymatic activities, involved in both glycolysis and OXPHOS, are upregulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…More recently, a Warburg effect has also been evidenced in arsenic-treated non-malignant pulmonary epithelial cell line BEAS-2B [223]. Furthermore, an upregulation of cell energy metabolism in B[a]P/arsenic-transformed lung epithelial cells has been reported [224]. Thus, it would be worth testing the role of NHE1 in the carcinogenic effects of arsenic as well as many other carcinogenic compounds, notably when present in chemical mixtures.…”
Section: Is Nhe1 Activation a General Phenomenon Upon Exposure To Envmentioning
confidence: 99%
“…More recently, a Warburg effect has also been evidenced in arsenic-treated non-malignant pulmonary epithelial cell line BEAS-2B [223]. Furthermore, an upregulation of cell energy metabolism in B[a]P/arsenic-transformed lung epithelial cells has been reported [224]. Thus, it would be worth testing the role of NHE1 in the carcinogenic effects of arsenic as well as many other carcinogenic compounds, notably when present in chemical mixtures.…”
Section: Is Nhe1 Activation a General Phenomenon Upon Exposure To Envmentioning
confidence: 99%
“…For another in rats, As 2 O 3 at a level of 5 mg/kg body weight (BW)/day elevated the levels of caspase-3 and nitric oxide and increased the expression of nucleic factor κB (NF-κB) p65 in the liver [ 6 ], which indicated the symptom of intoxication. Moreover, it has been also proved that longtime exposure to arsenic is deleterious to the liver [ 7 ], lung epithelial transformed cells [ 8 ], skin [ 9 ] and arsenic alters multiple cellular pathways, which include expression of cytokines, promotion and resistance of apoptosis and increasing oxidative stress [ 10 ], these alterations lead to disease manifestations. Recently, our studies have shown that subchronic exposure to As 2 O 3 in excess of 0.625 mg/kg BW causes inflammation, oxidative stress and heat shock response in the liver [ 11 ], brain [ 12 ] and immune organs [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, downregulation of glycolysis [ 23 ] or induction of mitochondria biogenesis [ 24 ] lead to the restoration of OXPHOS and subsequent death of malignant cells. Despite this common view, there are experimental data suggesting that high levels of OXPHOS are important to many cancer cells models and tumors [ 25 , 26 ].…”
Section: Specific Metabolic Alterations In Malignant Cellsmentioning
confidence: 99%